Living on the land: redesigning land use relationships in the Philippi Horticultural Area - Asmal, Saudah (School of Architecture, Planning and Geomatics, 2017)
Since the mid-1800's the Philippi Horticultural Area (PHA) has been of agricultural significance to Cape Town, producing food for the city. The Area also forms part of the remnant floodplain, and is essential in maintaining the recharge of the Cape Flats Aquifer, an important water source for Cape Town. Conflicting land use agendas are the major threat to resources in the PHA. Besides agriculture, there is an increasing demand on the City of Cape Town to provide housing in close proximity to the city centre. In light of this, re-zoning land in the PHA is being considered. While rezoning will address the demand for housing, it will put even further pressure on the current natural systems and water resources, as well as the historic presence of agriculture in the PHA. A new approach is required using landscape-based urban design to tackle what would usually be a planning predicament. Densification and development could be viable if they do not impact or encroach on the natural systems and agricultural land in the area, but rather help to sustain them. This requires introducing development typologies that work within the existing landscape and reconfiguring urban form to facilitate positive interfaces with both natural and agricultural systems. This project investigates integrating land use and experimentation with landscape and urban morphology as design tools in reconciling agendas, securing the agricultural and water resources in the PHA. The structuring land uses utilised are the urban fabric, agricultural land, natural systems and public open space. These are explored through a combination of geo-spatial mapping, collages, and a series of typologies that interrogate land use relationships in the PHA. Experimentation at multiple scales was used, a smaller area being used as a prototype for the larger area. Property lines significantly inform the framework for development, with consolidation and subdivision being the main tools for intervention. The project will re-organise the PHA in a way that enables mutually supportive land-use relationships, to secure the natural resources and function of the PHA while facilitating necessary development.